A comparison of salivary steroid levels during diagnostic tests for adrenal insufficiency - Dušková, Michaela; Šimůnková, Kateřina; Vítků, Jana; Kolátorová Sosvorová, Lucie; Jandíková, Hana; Pospíšilová, Hana; Šrámková, Monika; Kosák, Mikuláš; Kršek, Michal; Hána, Václav; Žánová, Magdalena; Springer, Drahomíra; et al. (Prague Medical Report, 2016)
Numerous diagnostic tests are used to evaluate the hypothalamic-pituitary-adrenal axis (HPA axis). The gold standard is still considered the insulin tolerance test (ITT), but this test has many limitations. Current guidelines therefore recommend the Synacthen test first when an HPA axis insufficiency is suspected. However, the dose of Synacthen that is diagnostically most accurate and sensitive is still a matter of debate. We investigated 15 healthy men with mean/median age 27.4/26 (SD±4.8) years, and mean/median BMI (body mass index) 25.38/24.82 (SD±3.2) kg/m2. All subjects underwent 4 dynamic tests of the HPA axis, specifically 1 μg, 10 μg, and 250 μg Synacthen (ACTH) tests and an ITT. Salivary cortisol, cortisone, pregnenolone, and DHEA (dehydroepiandrosterone) were analysed using liquid chromatography-tandem mass spectrometry. During the ITT maximum salivary cortisol levels over 12.5 nmol/l were found at 60 minutes. Maximum cortisol levels in all of the Synacthen tests were higher than this; however, demonstrating that sufficient stimulation of the adrenal glands was achieved. Cortisone reacted similarly as cortisol, i.e. we did not find any change in the ratio of cortisol to cortisone. Pregnenolone and DHEA were higher during the ITT, and their peaks preceded the cortisol peak. There was no increase of pregnenolone or DHEA in any of the Synacthen tests. We demonstrate that the 10 μg Synacthen dose is sufficient stimulus for testing the HPA axis and is also a safe and cost-effective alternative. This dose also largely eliminates both false negative and false positive results.
Keywords: pregnenolon; systém hypofýza - nadledviny; kosyntropin; Saliva; Healthy Volunteers; Dehydroepiandrosterone; diagnostické testy rutinní; Hormones; Pituitary-Adrenal System; mužské pohlaví; Adult; Adrenal Insufficiency; hydrokortison; sliny; Hydrocortisone; adrenální insuficience; hormony; Humans; chromatografie kapalinová; Cosyntropin; systém hypotalamus-hypofýza; Pregnenolone; dehydroepiandrosteron; dospělí; Chromatography, Liquid; Diagnostic Tests, Routine; lidé; Male; Hypothalamo-Hypophyseal System; zdraví dobrovolníci pro lékařské studie